1998
DOI: 10.1089/lap.1998.8.241
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric Migration of Laparoscopic Adjustable Gastric Band (Lap-Band) for Morbid Obesity

Abstract: The appearance of fistulas and the posterior intragastric inclusion of the adjustable silicone Lap-Band prothesis have been described, representing a severe complication of the Lap-Band procedure. A 45-year-old patient with severe obesity, weighing 115 kg, and having BMI (body max index) of 45 kg/m2 was assigned to a protocol to place a Lab-Band in her. An infection in the reservoir after 9 months indicated the beginning of the appearance of fistulas. The entire adjustable silicone gastric band device eroded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Band removal can be achieved by surgery (open or laparoscopic) or by endoscopy. In historical reports the removal of the intragastric migrated band was obtained by laparotomy followed by a gastrotomy [ 12 ]. However, laparoscopic approaches gained more and more attention because the minimally invasive technique leaves the abdominal cavity with fewer adhesions and in consideration of the fact that a future bariatric surgery may be needed [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Band removal can be achieved by surgery (open or laparoscopic) or by endoscopy. In historical reports the removal of the intragastric migrated band was obtained by laparotomy followed by a gastrotomy [ 12 ]. However, laparoscopic approaches gained more and more attention because the minimally invasive technique leaves the abdominal cavity with fewer adhesions and in consideration of the fact that a future bariatric surgery may be needed [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant reoperation rate due to band slippage [14,18]. Band repositioning due to slippage is a difficult laparoscopic procedure, which involves removal of the band from one position and reinsertion into another [1,6,7]. The 14 cases reported here were all corrected successfully, but all necessitated major laparoscopic procedures.…”
Section: Discussionmentioning
confidence: 87%
“…The gastric band can be surgically or endoscopically removed, including laparotomy and laparoscopic surgery. In 1998, it was reported that the gastric band could be removed via laparotomy [ 18 ]. With the increasing maturity of laparoscopic techniques, laparoscopic gastric band removal reduces the incidence of postoperative abdominal adhesions, which provides the possibility for later revision surgery, and has gradually become the primary surgical method for gastric band removal [ 19 ].…”
Section: Discussionmentioning
confidence: 99%